EXTRACELLULAR VESICLES AND MIRNAS IN BREAST CANCER: A SYSTEMATIC REVIEW ON PROFILES AND THEIR INFLUENCE ON TUMOR PROGRESSION - Oliveira, Jenniffer Dantas de; Jesus, Giovanna Gomes de; Assunção, Joyce Gabrielle Ramos; Sousa, Mickael Breno Godoi; Toledo e Silva, Esther Duarte; Afonso, João Pedro (CIPEEX, 2025)
Breast cancer remains one of the major challenges in global public health, owing to its high incidence and biological heterogeneity. Among the diverse mechanisms underlying its progression, intercellular communication plays a pivotal role, largely mediated by extracellular vesicles (EVs). These nanoscale structures function as messengers, transporting a wide range of biomolecules—such as proteins, lipids, and RNAs—between cells within the tumor microenvironment. Within the cargo of EVs, microRNAs (miRNAs) have emerged as key regulators. These small non-coding RNA molecules modulate gene expression at the post-transcriptional level. Recent evidence demonstrates that EV-associated miRNAs released by tumor cells influence multiple hallmarks of carcinogenesis, including cell proliferation, apoptosis evasion, invasion, angiogenesis, and therapeutic resistance. In this context, the present study aims to perform a systematic literature review to map the profiles of miRNAs contained in EVs secreted by breast cancer cells, and to elucidate their role in biological processes associated with tumor progression. The methodology is based on comprehensive searches conducted under strict inclusion and exclusion criteria. The expected outcomes include the identification of key miRNAs differentially expressed in EVs, as well as the characterization of their functional relevance. Such insights may provide the foundation for the development of novel therapeutic strategies and prognostic biomarkers for breast cancer.